QUALIFICATION DATA AS A BASIS FOR TEACHER TRAINING DISTANCE LEARNING - Natalia V. Nikulicheva (Открытое образование (Москва), 2016)
At present, the professional status of the teacher of distance education as well as his professional requirements and characteristics is not officially presented in Russian pedagogics: either his functions, or requirements to knowledge and requirements to qualification. Occurrence of such regulations will help to develop uniform requirements for preparation and retraining of the distance-learning teacher, specifications under the account and control of his pedagogical activity, new economic system of payment of the distance-learning teacher, adequate to its true expenditures of labor.